Candida albicans impairs macrophage function and facilitates Pseudomonas aeruginosa pneumonia in rat - Roux, Damien; Gaudry, Stéphane; Dreyfuss, Didier; El-Benna, Jamel; de Prost, Nicolas; Denamur, Erick; Saumon, Georges; Ricard, Jean-Damien (Critical care medicine, 2009)
To determine whether Candida albicans airway colonization influences Pseudomonas aeruginosa pneumonia prevalence in rats and by which mechanism. Prospective, randomized, controlled animal study. Research laboratory of a university. Male adult Wistar rats weighing 275-300 g. In vivo: P. aeruginosa pneumonia was induced by bronchial instillation of P. aeruginosa in rats previously instilled or not with live or ethanol-killed C. albicans. In vitro: Alveolar macrophages were incubated with or without live or ethanol-killed C. albicans. Quantitative cultures of lung were done. Lung tumor necrosis factor alpha, interferon gamma, and interleukin-6 levels were measured along with reactive oxygen species (ROS) production by alveolar macrophages. P. aeruginosa pneumonia prevalence was higher in rats given live but not ethanol-killed C. albicans. Instilling live C. albicans alone increased lung tumor necrosis factor-alpha and interferon-gamma but not interleukin-6, and was not associated with clinical or histologic signs of infection. These three cytokines were more abundant in lungs instilled with live C. albicans and P. aeruginosa than in those instilled with P. aeruginosa alone or with ethanol-killed C. albicans and P. aeruginosa. Alveolar macrophages incubated with live C. albicans had decreased ROS production. C. albicans impedes alveolar macrophage ROS production and is correlated with an increase of P. aeruginosa pneumonia prevalence in rats. These results highlight the previously overlooked impact of airway fungal colonization on lung bacterial infection, and indicate the need for studies on the potential for antifungal therapy to prevent the onset of ventilator-associated pneumonia caused by P. aeruginosa.